Surgical management of negative dysphotopsia. Issue 1 (January 2018) - Masket, Samuel; Fram, Nicole R.; Cho, Andrew; Park, Isaac; Pham, Don
Abstract : Purpose : To evaluate curative and preventative surgical strategies for negative dysphotopsia. Setting : Private practice, Los Angeles, California, USA. Design : Retrospective case series. Methods : Patients with self‐reported chronic negative dysphotopsia had corrective surgery as the therapeutic group. Second eye surgery, in cases with negative dysphotopsia in the previously operated eye, comprised the preventative group. Chronologically, several surgical strategies were used, including bag‐to‐bag intraocular lens (IOL) exchange, reducing posterior chamber depth, piggyback secondary IOL placement, bag‐to‐sulcus IOL exchange, and reverse optic capture. The primary outcome measure was improvement of negative dysphotopsia by 3 months postoperatively. Results : The therapeutic group comprised 40 eyes of 37 patients; 76.6% of causative IOLs were acrylic and 23.4% were silicone and all were bag‐fixated. There were 21 eyes in the preventative group of which 11 were second eyes from the therapeutic group; the remaining 10 did not require surgery for the symptomatic eye. Successful outcomes for each surgical strategy were as follows: bag‐to‐bag IOL exchange (0/5), a reduction in posterior chamber depth with iris suture fixation of the bag–haptic complex (0/1), piggyback secondary IOL (8/11), secondary reverse optic capture (21/22), ciliary sulcus posterior chamber IOL exchange (7/8), and primary reverse optic capture (21/21). Conclusions : Negative dysphotopsia was associated with acrylic or silicone IOLs of either square‐ or round‐edge design. Negative dysphotopsia was reduced, eliminated, or prevented when the IOL optic overlaid the anterior capsulotomy rather than when the capsule edge overlaid the optic. Bag‐to‐sulcus IOL exchange and reverse optic capture were highly successful in managing or preventing negative dysphotopsia.